The Use of Kahoot to Improve Students' Grammar at SMA Insan Cendekia Syech Yusuf - Besse Siska Ulfia Ningsih; Maemuna Muhayyang (PT ARRUS Intelektual Indonesia, 2024)
The purpose of this study is to find out whether or not Kahoot improves students' grammar. This research used quantitative methods). The population of this study was the eleventh-grade students of SMA Insan Cendekia Syech Yusuf, using cluster random sampling technique selects 40 students as the sample of this study. To obtain the required data, it used grammar tests. Its results showed that Kahoot is effective in helping the students improve their grammar by some criteria. 1. The N-gained score of the experimental class (53.14) was higher than the N-gain score of the control class (49.26). 2. Based on the criteria for achieving learning objectives (KKTP), the percentage of students in the experimental class who obtained scores above 75 was 100%, while it was 89% in the control class. Finally, the hypothesis testing pointed out that t-test value > t-table shows that Ha is accepted and Ho is rejected and meaning that Kahoot is effective in improving students' grammar. Based on those results, it is considerable that the use of Kahoot effectively gave significant results in the grammar improvement of the students at SMA Insan Cendekia Syech Yusuf.